
Algebra PreAlgebra and Basic Algebra Math Forum 
 LinkBack  Thread Tools  Display Modes 
March 29th, 2010, 12:54 PM  #1 
Newbie Joined: Mar 2010 Posts: 1 Thanks: 0  Prove CK equation using markov chain definition
Could somebody tell me how to prove CK equation in formal methods using markov chain definition? In almost all the books that I have read, the CK equation is said to be proved as following steps: P{Xn = xnX0 = x0} = ?n i=0 P{Xn = xnXn1 = xn1,Xi = xi}* P{Xn1 = xn1Xi = xi} = ?n i=0 P{Xn = xnXn1 = xn1}* P{Xn1 = xn1Xi = xi} It is said that P{Xn = xnXn1 = xn1,Xi = xi} = P{Xn = xnXn1 = xn1}* P{Xn1 (1) is because we have the markov chain definition. However, we know, markov chain is defined as: P{Xn = xnXn1 = xn1} = P{Xn = xnXn1 = xn1, Xn2 = xn2, ..., X0 = x0} In formal method, I express Xn1 = xn1, Xn2 = xn2, ..., X0 = x0 logically as their intersection as it defined in math. I'm not sure if the definition is correct or there are some further steps before getting (1). Could anybody help me to answer this question? Or give me some clues (like reference, or guide)? Thanks! 

Tags 
chain, definition, equation, markov, prove 
Search tags for this page 
Click on a term to search for related topics.

Thread Tools  
Display Modes  

Similar Threads  
Thread  Thread Starter  Forum  Replies  Last Post 
Help with Hidden Markov chain  dr_romix  Advanced Statistics  2  October 16th, 2012 06:36 PM 
help in markov chain  legendoulis  Advanced Statistics  4  April 4th, 2012 11:28 AM 
Markov Chain problem  450081592  Advanced Statistics  1  March 6th, 2012 04:17 PM 
Markov chain  butabi  Advanced Statistics  1  February 12th, 2012 03:20 PM 
Markov Chain matrix  Turloughmack  Linear Algebra  0  February 7th, 2011 05:15 AM 